1986
DOI: 10.1080/05698198708981779
|View full text |Cite
|
Sign up to set email alerts
|

Piezoviscous Effects in Nonconformal Contacts Lubricated Hydrodynamically

Abstract: ABSTRACT' "'* The analysis 1n this paper 1s concerned with the p1ezov1scous-r1g1d regime of lubrication for the general case of elliptical contacts. In this regime several formulas of the lubricant film thickness have been proposed by Hamrock and Dowson, by Dowson et al., and more recently by Houpert. However, either they do not Include the load parameter W, which has a strong effect on film thickness, or they overestimate the film thickness by using the Barus formula for pressure-viscosity characteristics. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This occurs rarely in practical applications but it has been suggested that it may be present in roller end-guide flanges in moderately highly loaded cylindrical tapered roller bearings [10] Considerable numerical modelling work has been carried out to solve combinations of the Reynolds, elastic deformation and piezoviscosity equations and thus develop regression equations to predict both central and minimum film thickness in all of the above four hydrodynamic regimes [4][5][6][7]. For the circular point contact of interest to the current study, …”
Section: Introductionmentioning
confidence: 99%
“…This occurs rarely in practical applications but it has been suggested that it may be present in roller end-guide flanges in moderately highly loaded cylindrical tapered roller bearings [10] Considerable numerical modelling work has been carried out to solve combinations of the Reynolds, elastic deformation and piezoviscosity equations and thus develop regression equations to predict both central and minimum film thickness in all of the above four hydrodynamic regimes [4][5][6][7]. For the circular point contact of interest to the current study, …”
Section: Introductionmentioning
confidence: 99%
“…In a completely different way, Venner [28] and Chevalier [29] later obtained very close asymptote equations for both central and minimum film thicknesses from numerical EHD solvers. Finally, Jeng et al [33] published a numerical expression to describe the PR regime. All the equations mentioned can be written as follows for fully flooded circular lubricated point contacts: one note that the Venner and Chevalier equations for It was easy to check by eye from the interferograms that fully flooded conditions applied during tests conducted in the EHD regime and in the transition from EHL towards hydrodynamic lubrication.…”
Section: Resultsmentioning
confidence: 99%
“…II F), the magnitude of _ c zy ( _ c xy . 22 We summarize the modified viscosity approach as a system of equations comprising of a single non-linear Reynolds equation and an expression for the modified viscosity, @ @x h 3 12…”
Section: Modified Viscosity Approachmentioning
confidence: 99%
“…1 The second major effect due to the pressure is piezoviscosity, which is the possibility of the lubricant viscosity to increase due to the large pressure. 3 The intertwining of the polymer molecules as they are brought closer to each other due to the pressure leads to an increase in the flow resistance, which results in a higher viscosity. 4 This relationship is not linear and is generally explained by using empirical relations obtained from experimental data.…”
Section: Introductionmentioning
confidence: 99%